2022
DOI: 10.1007/s11625-022-01200-4
|View full text |Cite
|
Sign up to set email alerts
|

Managing biodiversity in the Anthropocene: discussing the Nature Futures Framework as a tool for adaptive decision-making for nature under climate change

Abstract: Conservation approaches to social-ecological systems have largely been informed by a framing of preserving nature for its instrumental societal benefits, often ignoring the complex relationship of humans and nature and how climate change might impact these. The Nature Futures Framework (NFF) was developed by the Task Force on scenarios and models of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services as a heuristic approach that appreciates the diverse positive values of nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 80 publications
0
5
0
1
Order By: Relevance
“…Other recent advancements on the applications of the NFF include its coupling with quantitative modelling of landscape scenarios (Haga et al 2023) and methodological guidance to develop illustrative scenarios (Durán et al 2023). Recent studies also indicate how the NFF can be applicable to contexts beyond scenarios, including the assessment of management strategies and policies (e.g., Palacios-Abrantes et al 2022; Kim et al 2023; Stronge et al 2023).…”
Section: Framework That Inform Participatory Scenario Planningmentioning
confidence: 99%
“…Other recent advancements on the applications of the NFF include its coupling with quantitative modelling of landscape scenarios (Haga et al 2023) and methodological guidance to develop illustrative scenarios (Durán et al 2023). Recent studies also indicate how the NFF can be applicable to contexts beyond scenarios, including the assessment of management strategies and policies (e.g., Palacios-Abrantes et al 2022; Kim et al 2023; Stronge et al 2023).…”
Section: Framework That Inform Participatory Scenario Planningmentioning
confidence: 99%
“…De instrumentele waarde refereert ook aan de waarde die gehecht wordt aan bepaalde ecosysteemdiensten die de natuur levert aan mensen, zoals waterzuivering, klimaatregulatie en bestuiving van gewassen. c) Binnen de relationele waarde [12][13][14][15] wordt natuur gewaardeerd vanwege de relaties en interacties die mensen individueel en collectief hebben met de natuur. Deze kunnen zeer uiteenlopend zijn, en zowel positief als negatief zijn.…”
Section: Normatieve Dimensie: Waardenunclassified
“…However, it is essential to note that some studies have found no general cognitive advantages for bilingual individuals1. For instance, a population study of 11,000 people found that bilinguals showed an advantage over monolinguals on only one test, and these effects disappeared when the groups were matched to remove potentially confounding factors [19] [13]. Despite these findings, the potential cognitive and social implications of bilingualism and multilingualism remain an area of interest in academic research.…”
Section: Bilingualismmentioning
confidence: 99%